2018
DOI: 10.1111/ases.12640
|View full text |Cite
|
Sign up to set email alerts
|

Safety of laparoscopic colorectal surgery in patients with ventriculoperitoneal shunt

Abstract: Our study suggests that laparoscopic colorectal surgeries in patients with VPS without any manipulations may be safe. Future studies should aim to better standardize the perioperative management of VPS during laparoscopic colorectal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…Laparoscopic surgery in patients with VPS has been reported in cholecystectomy [3][4][5][6][7], salpingectomy [8], ileocecal resection [9], colectomy [2,10], gastrectomy [10], adrenal adenoma excision [11], stomas, cystoplasty, bladder neck reconstruction, testicular vessel clipping and fascial slinging [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Laparoscopic surgery in patients with VPS has been reported in cholecystectomy [3][4][5][6][7], salpingectomy [8], ileocecal resection [9], colectomy [2,10], gastrectomy [10], adrenal adenoma excision [11], stomas, cystoplasty, bladder neck reconstruction, testicular vessel clipping and fascial slinging [12].…”
Section: Discussionmentioning
confidence: 99%
“…Neale and Falk reported that the modern anti-reflux systems had not shown any retrograde flow when exposed to pressures as high as 350 mmHg in an in-vitro experiments [15]. Thus, the clamping or externalization of the shunt catheter is probably unnecessary, and on the other hand, whether clamping of the shunt could actually exacerbate increases in ICP is not known [2]. Uzzo, et al described the results of intraoperative intracranial pressure monitoring in 2 patients in whom intracranial pressure increased promptly at abdominal insufflation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that all cases experienced an uneventful postoperative course, with no shunt-associated complications. A retrospectively from japan reported safe laparoscopic colorectal surgery in four patients with VP shunt who were operated with the pneumoperitoneum pressure set at 10 mmHg under routine anesthetic monitoring and without any manipulations such as clamping or externalization of the VP catheters [51]. One case of VP shunt failure in a patient with shuntdependent hydrocephalus after laparoscopic placement of feeding jejunostomy was reported by Baskin et al [52] postoperatively; the patient developed clinical and radiographic evidence of shunt failure and underwent emergent shunt revision that revealed an isolated distal shunt obstruction.…”
Section: Laparoscopic Surgery In Patients With Vp Shuntsmentioning
confidence: 99%
“…Other concerns include shunt dysfunction 4 and shunt infection/retrograde meningitis 5,6 . Several previous case reports have demonstrated the safety of laparoscopic surgery in patients with a VPS or LPS; however, perioperative shunt management has differed between the various reports 7–32 …”
Section: Introductionmentioning
confidence: 99%